DF-Fit: a robust algorithm for detection of crystallographic information in atom probe tomography data - Haley, D; Bagot, PAJ; Moody, MP (Oxford University Press, 2019)
We report on a new algorithm for the detection of crystallographic information in three-dimensional, as retained in atom probe tomography (APT), with improved robustness and signal detection performance. The algorithm is underpinned by one-dimensional distribution functions (DFs), as per existing algorithms, but eliminates an unnecessary parameter as compared to current methods.